53 Real world experience with anti-thrombotics after percutaneous intervention in patients with an indication for an oral anticoagulant. (16th October 2019) - Tanner, R; Cronin, M; Macken, L; Matiullah, S; O'Connor, S; Ullah, I; Cosgrave, J; Maree, A; Murphy, R; Foley, B; Daly, C
Abstract : Introduction: The appropriate anti-thrombotic regime after a percutaneous intervention (PCI) for patients who have an indication for an oral anticoagulant (OAC) is not standardised and represents a challenge to clinicians who are guided by a patient's perceived bleeding and ischaemic risks. Hence, we sought to describe our current clinical practice for patients undergoing PCI with an OAC indication. Methods: A retrospective review of patient's clinical notes was performed to identify those discharged with an indication for an OAC after PCI between October 2018 and March 2019. These patients were further scrutinised for the antithrombotic-OAC regime employed, bleeding risk and ischaemic risk. Results: Over a 6-month period, 9.7% (n=69) of patients (14.5% female, mean age 71.2±9.7 years, 9.7% ACS presentation) undergoing PCI had an indication for an OAC on discharge. Atrial fibrillation (AF) was the OAC indication in 84% of cases (n=58) and these patients had a mean CHA2DS2-VASc score of 3.6±1.2 and mean HAS-BLED score of 2±0.6. Standard drug-eluting stents were deployed in the majority of cases while Polymer-free BioFreedom stents were used for 31.9% (n=22) of patients. A variety of antithrombotic-OAC regimes were prescribed on discharge, table 1. Dual antiplatelet therapy (DAPT) without an OAC was prescribed for 2 patients on discharge who experienced inpatient bleeding complications. Apixaban and rivaroxaban were prescribed for 43.5% (n=30) and 36.2% (n=25) of patients respectively on discharge, warfarin was prescribed for a minority of patients (6.9%, n=6). DAPT with an OAC was prescribed for a mean of 7.4±5.3 weeks (range 4 –> 26 weeks) in 81% (n=56) of patients. Once the planned duration of combination DAPT-OAC was complete, clopidogrel was continued as the single antiplatelet of choice in addition to an OAC in 50% (n=28) of cases. For patients with AF, a discharge regime of an OAC with clopidogrel in the absence of aspirin did not appear to be related to patient's CHA2DS2-VASc or HAS-BLED score. This pattern was operator dependent. Bleeding and ischaemic rates at 6-month follow up are pending. Conclusions: A clear preference for novel OACs after PCI was observed. However, the choice of antithrombotic and duration of OAC was highly variable. This likely reflects the challenge in assessing individuals bleeding and ischaemic risks.